PlA2 Polymorphism of Platelet Glycoprotein IIb/IIIa and C677T Polymorphism of Methylenetetrahydrofolate Reductase (MTHFR), but Not Factor V Leiden and Prothrombin G20210A Polymorphisms, Are Associated with More Severe Forms of Legg-Calvé-Perthes Disease - María Dolores García-Alfaro; María Isabel Pérez-Nuñez; María Teresa Amigo; Carmelo Arbona; María Ángeles Ballesteros; Domingo González-Lamuño (MDPI AG, 2021)
The possible association of common polymorphic variants related to thrombophilia (the rs6025(A) allele encoding the Leiden mutation, rs1799963(A), i.e., the G20210A mutation of the prothrombin F2 gene, the rs1801133(T) variant of the methylenetetrahydrofolate reductase (MTHFR) gene that encodes an enzyme involved in folate metabolism, and rs5918(C), i.e., the 'A2' allele of the platelet-specific alloantigen system that increases platelet aggregation induced by agonists), with the risk of Legg-Calvé-Perthes disease (LCPD) and the degree of hip involvement (Catterall stages I to IV) was analyzed in a cohort study, including 41 children of ages 2 to 10.9 (mean 5.4, SD 2.2), on the basis of clinical and radiological criteria of LCPD. In 10 of the cases, hip involvement was bilateral; thus, a total of 51 hips were followed-up for a mean of 75.5 months. The distribution of genotypes among patients and 118 controls showed no significant differences, with a slightly increased risk for LCPD in rs6025(A) carriers (OR: 2.9, CI: 0.2-47.8). Regarding the severity of LCPD based on Catterall classification, the rs1801133(T) variant of the MTHFR gene and the rs5918(C) variant of the platelet glycoprotein IIb/IIIa were associated with more severe forms of Perthes disease (Catterall III-IV) (p < 0.05). The four children homozygous for mutated MTHFR had a severe form of the disease (Stage IV of Catterall) and a higher risk of non-favorable outcome (Stulberg IV-V).